The psychological characteristics of football players under the age of 17 in Indonesia - Zulakbal bin Abd Karim, Jaffry bin Zakaria, Thariq Khan bin Azizuddin Khan, Noorzaliza binti Osman (Tanjung Malim, 2024)
The psychological characteristics of football players under the age of 17 in Indonesia by Zulakbal bin Abd Karim, Jaffry bin Zakaria, Thariq Khan bin Azizuddin Khan, Noorzaliza binti Osman